Pengaruh Media Pembelajaran Berbasis Canva Terhadap Hasil Belajar Matematika Siswa - Prawangsa, Khofifah Indra Prawangsa; Sripatmi; Novitasari, Dwi; Turmuzi, Muhammad (Mandalika Mathematics and Educations Journal, 2024)
This study aims to determine whether or not there is an effect of using Canva learning media on student learning outcomes in class XI circle material at SMK Negeri 3 Selong. This research is an experimental research with quasi experimental design. The study population was the XI grade students of SMK Negeri 3 Selong as many as 4 classes. The research sample was two classes, namely the experimental class using Canva-based learning media and the control class using conventional media taken using cluster random sampling. Data collection techniques using observation and tests. As for the instrument validity test, it was carried out with the content validity test which was calculated using the Aiken's V index. Data analysis carried out is normality test, homogeneity test, hypothesis test, and effect size test to see whether there is an effect of Canva-based learning media on student learning outcomes on circle material. The results showed t_hitung (2.661) > t_table (2.01), the effect size test results were 0.757 and the average value of the posttest results of the class using Canva-based learning media was higher than the class using conventional media. So it can be concluded that learning by using Canva-based learning media has an effect on student learning outcomes in circle material class XI SMK Negeri 3 Selong academic year 2024/2025.